Anti-inflammatory Effects of Novel Thiazolidinone Derivatives as Bioactive Heterocycles on RAW264.7 Cells - Hossein Ghafoori; Mehrnaz Rezaei; Asadollah Mohammadi (Iranian Journal of Allergy, Asthma and Immunology, 2017)
The inhibition of the inducible nitric oxide synthase (iNOS), cyclooxygenase 2 (COX-2) and nuclear factor-κB (NF-κB) production are research targets of attract in the field of anti-inflammatory drug development. Therefore, this study was designed to investigate the anti-inflammatory effects of novel thiazolidinone derivatives using a cellular model of lipopolysaccharide (LPS)-stimulated murine macrophage RAW 264.7. In the present study, five new derivatives (A to E) of thiazolidinone were synthesized and screened for anti-inflammatory activities. Cell viability of LPS-stimulated RAW 264.7 macrophages clearly decreased in >55 μg/mL of synthesized A-E compounds especially in the presence of C; therefore, up to 50 μg/mL of compounds were selected for the subsequent analysis. A majority of these compounds showed significant inhibition on the production of NO in LPS-stimulated macrophages in a dose-dependent manner. Compounds B and D (10-50 μg/mL) significantly inhibited LPS-induced NF-κB (p65) production in a dose-dependent manner. The effects of B and D on iNOS and COX-2 mRNA and protein expression in LPS-stimulated RAW 264.7 cells were detected by real time-PCR and western blot. B derivative significantly suppressed the iNOS and COX-2 mRNA level and as well as protein expression. Taken together, these results reveal that compound B as new thiazolidinone derivative decreased expression of the inflammatory-related signals (NO, iNOS and COX-2) through regulation of NF-κB; hence, this compound could be suggested as a novel therapeutic strategy for inflammation-associated disorders.